Eosinophil Proportion May Serve as a Candidate Biomarker for Adverse Events in Patients With Urothelial Carcinoma Treated With Enfortumab Vedotin - Kunihiro Odagiri; Toshiharu Morikawa; Taku Naiki; Yosuke Sugiyama; Yoshihiko Tasaki; Yoshihisa Mimura; Aya Naiki‐Ito; Takashi Nagai; Toshiki Etani; Keitaro Iida; Daiki Ishikawa; Yusuke Noda; et al. (Cancer Medicine, 2026)
ABSTRACT Enfortumab vedotin (EV) is a crucial treatment for patients with metastatic urothelial carcinoma (mUC). However, a significant proportion of patients experience adverse events (AEs). The identification of biomarkers for AEs is imperative for the detection and treatment of AEs at an early stage. In this exploratory study, we aimed to identify biomarkers of AEs in patients with mUC treated with EV. We retrospectively examined 10 factors identified from the data of 116 patients with mUC treated with EV to identify biomarkers (age, body mass index, C‐reactive protein level, Eastern Cooperative Oncology Group performance status, eosinophil proportion, history of diabetes, lymphocyte proportion, neutrophil proportion, neutrophil‐to‐lymphocyte ratio, and platelet count) associated with the occurrence of AEs of any grade. The candidate biomarkers were measured at the start of EV treatment. The least absolute shrinkage and selection operator method was used to select the most useful parameters for predicting AE occurrence. Among the 10 factors, eosinophil proportion was identified as the only potential biomarker. The optimal cutoff value for eosinophil proportion against the occurrence of AEs of any grade was 2.5% (area under the curve = 0.625). Univariable logistic regression analyses showed that an eosinophil proportion of ≥ 2.5% was a risk factor for AE development (odds ratio = 4.35, 95% confidence interval = 1.35–14.0). Therefore, the results of this exploratory study indicated that an eosinophil proportion of ≥ 2.5% at the start of EV treatment may be a candidate biomarker for the occurrence of AEs of any grade.